2009
DOI: 10.1186/1471-2334-9-104
|View full text |Cite
|
Sign up to set email alerts
|

Role of pathogenic oral flora in postoperative pneumonia following brain surgery

Abstract: BackgroundPost-operative pulmonary infection often appears to result from aspiration of pathogens colonizing the oral cavity. It was hypothesized that impaired periodontal status and pathogenic oral bacteria significantly contribute to development of aspiration pneumonia following neurosurgical operations. Further, the prophylactic effects of a single dose preoperative cefazolin on the oral bacteria were investigated.MethodsA matched cohort of 18 patients without postoperative lung complications was compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
1
30
0
4
Order By: Relevance
“…Of 23 patients evaluated after brain surgery [16], 5 developed postoperative aspiration pneumonia and were compared to the other 18 patients without postoperative lung complications with respect to their preoperative periodontal status and oral bacterial profile. Preoperative dental exams were performed to quantify the severity of the periodontal disease using a numeric scoring system.…”
Section: Association Between Oral Hygiene and Pneumoniamentioning
confidence: 99%
“…Of 23 patients evaluated after brain surgery [16], 5 developed postoperative aspiration pneumonia and were compared to the other 18 patients without postoperative lung complications with respect to their preoperative periodontal status and oral bacterial profile. Preoperative dental exams were performed to quantify the severity of the periodontal disease using a numeric scoring system.…”
Section: Association Between Oral Hygiene and Pneumoniamentioning
confidence: 99%
“…Oral mucositis and esophagitis commonly affect patients with hematologic malignancies or those receiving stem cell transplantation, also causing impairments of swallow function that result in bacterial pneumonias. Interestingly, while the oral microbial diversity of cancer patients does not much differ from the general population, the incidence of periodontal disease is significantly greater in those undergoing cancer chemotherapy [47-49]. It has been subsequently suggested that optimized dental care in patients receiving chemotherapy may reduce the incidence of aspiration events and reduce the frequency of fever, productive cough and positive blood cultures [50].…”
Section: Introductionmentioning
confidence: 99%
“…Oral bacteria are reported pathogens for pneumonia (El-Solh et al, 2004;Terpenning et al, 2001), and periodontitis severity has been associated with pneumonia mortality (Awano et al, 2008) and postoperative pneumonia onset (Bagyi et al, 2009). Pneumonia is also highly prevalent among postoperative infections in patients undergoing major heart surgery (Bouza et al, 2006;Hortal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As a chronic oral inflammatory disease, periodontitis has strong associations with diabetes, arteriosclerotic disease, rheumatism, infective endocarditis (IE), pneumonia, and other systemic inflammatory conditions (Bagyi et al, 2009;Hajishengallis, 2015;Nishimura et al, 2017;Saengtipbovorn & Taneepanichskul, 2014;Sfyroeras, Roussas, Saleptsis, Argyriou, & Giannoukas, 2012). Bacteremia develops easily in patients with periodontitis with dental treatment, tooth brushing, or even mastication (Nishimura et al, 2017) when periodontal bacteria penetrate into the microvessels of periodontal pockets.…”
Section: Introductionmentioning
confidence: 99%